A Cross-Sectional Survey Study among Hand Surgeons in the United States on Standardizing Microsurgery Training - Mehrzad, Raman; Prsic, Adnan; Basta, Marten; Bhatt, Reena (Journal of Hand and Microsurgery, 2019)
Although microsurgery plays a more expansive role in hand surgery, microsurgery training systems may not have followed the same evolution, as have other operative techniques. A cross-sectional survey study with 13 multiple choice questions was administered to the members of the American Society for Surgery of the Hand; 503 out of 3,395 responded to the survey (14.8% response rate), and 58% did not have a microsurgical laboratory in their institution, whereas 42% did. Of the institutions that had a microsurgical laboratory, 32.4% also had a microsurgical rat laboratory. Of all respondents, 78% agreed or strongly agreed that their training program should have microsurgery training outside of the operating room, and 53% agreed or strongly agreed that their curriculum needed improvement; 65.6% agreed or strongly agreed that training should be standardized across the nation. Our results indicate that the training needs standardization and that institutional training curriculum needs to be improved. This is a Level III study.
Keywords: microsurgery; hand and upper extremity surgery; training; curriculum; education